Use of an osteoconductive compound as an aid in the management of a maxillary fracture in a boa constrictor - Rahal, Sheila C. [UNESP]; Teixeira, Carlos R. [UNESP]; Vulcano, Luiz C. [UNESP]; Aguiar, Antonio J. A. [UNESP] (My University, 2011)
A boa constrictor was presented with a short oblique compound fracture of the rostral third of the right maxilla. The fracture was reduced and biomaterial was placed around the fracture. A computed tomography scan at 1.5 mo post-surgery showed that the fracture had healed with slight displacement of the bone fragments.